Religion, Science, and Culture: An Integrated, Interconnected Paradigm of Science - Abdullah, M. Amin (Al-Jamiah: Journal of Islamic Studies, 2014)
Discussing the paradigm of dialogue and integration in the Islamic science of religion is important since the practice of religious education still applies the paradigm of conflict and independence. These paradigms have a great influence on the formation of socio-religious and cultural ways of thinking. The relationship between Islamic religiousc and natural, social, as well as cultural sciences, needs patterns of integrated, interconnected relations and dialogues. Islamic Studies requires a multidisciplinary approach, that is, interdisciplinarity and transdisciplinarity. Scientific linearity, in which science is narrowly defined and mono-disciplinary, will lead to an understanding of religion and religious interpretations that has no contact with and relevance to the context in which it is studied. New types of religious thought that encourage independent discussion and dialogue on the subjective, objective and intersubjective aspects of science and religion will create the emergence of a new type of religiosity in the multicultural era. All of this requires more effort to undertake a serious reconstruction of scientific methodologies and the methodologies of scientific studies of religion.[Penerapan paradigma dialog dan integrasi dalam ilmu-ilmu keislaman masih penting untuk didiskusikan mengingat praktik pendidikan agama masih menerapkan paradigm konflik dan independen. Paradigma-paradigma ini memiliki pengaruh yang besar dalam pembentukan cara pandang keagamaan, baik sosial maupun kultural. Hubungan antara ilmu-ilmu keislaman di satu sisi dengan ilmu-ilmu alam, sosial, dan budaya di sisi lain, memerlukan pola hubungan dan dialog yang terintegrasi-interkoneksi. Studi Islam mensyaratkan pendekatan multi disiplin, baik interdisipliner maupun transdisipliner. Linearitas keilmuan yang membatasi bidang ilmu secara sempit dan mono-disiplin akan menggiring pemahaman agama dan tafsir keagamaan yang tidak terkait dan tidak relevan dengan konteks pengkajian. Model baru pemikiran keagamaan yang mendorong dialog dan diskusi yang independen mengenai aspek-aspek subjektif, objektif, dan intersubjektif ilmu dan agama akan menciptakan munculnya model baru keberagamaan di era multicultural. Semua ini memerlukan lebih banyak upaya serius dalam merekonstruksi metodologi keilmuan dan metode-metode studi agama.]